KUALITAS FISIK DAGING BROILER DI PASAR MODERN KOTA BANDAR LAMPUNG - Akhmad Rangga; Khaira Nova; RR Riyanti (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to determine the physical quality of broiler meat including pH value, water holding capacity, and cooking losses in the modern market of Bandar Lampung City. This research was conducted on Januari-March 2020. The research material was breast fillet meat. Samples came from six modern markets in the city of Bandar Lampung (Mall Boemi Kedaton, Transmart, Central Plaza, Chandra Teluk, Chandra Karang, and Mall Kartini). The variables observed in this study were the degree of acidity (pH), water holding capacity (DIA), and cooking losses. The results of this study indicated that the degree of acidity (pH) in the modern market of Bandar Lampung City ranged from 6,109-6,386. The DIA value in the modern city market Bandar Lampung ranges from 61,157-68,021%, the value of cooking losses in the modern market of Bandar Lampung City ranges from 30,032-39,494%. The results of this study indicate that the pH, DIA, and cooking losses have met the standards for consumption in the six modern markets in the city of Bandar Lampung. Keywords: Broiler, Modern market, Degree of acidity (pH), Water holding capacity (DIA), Cooking losses.